Effect of the Association of Nonsteroidal Anti-inflammatory and Antibiotic Drugs on Antibiofilm Activity and pH of Calcium Hydroxide Pastes - Freitas, Rafaela Pignatti de; Greatti, Vanessa Raquel [UNESP]; Alcalde, Murilo Priori; Cavenago, Bruno Cavalini; Vivan, Rodrigo Ricci; Hungaro Duarte, Marco Antonio; Villas Boas Weckwerth, Ana Carolina; Weckwerth, Paulo Henrique (Elsevier B.V., 2017)
Introduction: The objective of the present study was to evaluate the in vitro antibiofilm activity and pH of calcium hydroxide associated with different nonsteroidal anti-inflammatory drugs (NSAIDs). Methods: The groups analyzed were as follows: group 1, calcium hydroxide paste with propylene glycol; group 2, calcium hydroxide paste with propylene glycol + 5% diclofenac sodium; group 3, calcium hydroxide paste with propylene glycol + 5% ibuprofen; group 4, calcium hydroxide paste with propylene glycol + 5% ciprofloxacin; and group 6, positive control (without medication). For analysis of the pH, the pastes were inserted into tubes and immersed in flasks containing ultrapure water. At the time intervals of 3, 24, 72, and 168 hours, the pH was measured with a calibrated pH meter. For microbial analysis, biofilm was induced in 30 bovine dentin blocks for 21 days. Subsequently, the pastes were placed on the blocks with biofilm for 7 days. Afterward, the pastes were removed by irrigation with sterile water, and the specimens were analyzed with a laser scanning confocal microscope with the 50 mu L Live/Dead BacLight Bacterial Viability solution L7012 Kit (Molecular Probes, Inc, Eugene, OR). Data were subjected to statistical analysis at a significance level of 5%. Results: The highest pH values were found for calcium hydroxide associated with ciprofloxacin in all periods analyzed. With the exception of pure calcium hydroxide paste, the other groups showed statistically significant differences (P <.05) in comparison with the positive control. Conclusions: The association of NSAIDs or antibiotic did not interfere with the pH of calcium hydroxide paste and increased the antimicrobial action of calcium hydroxide paste against Enterococcus faecalis biofilm formation.
Keywords: Antibiofilm action; calcium hydroxide; diclofenac; ibuprofen; intracanal medication